Brugte de virkelig en nål? - Bülow-Jacobsen, Ad (AIGIS, 2024)
It is proposed to emend Pliny, NH XIII 74 diviso acu into diviso accurate. A needle is unsuitable for peeling off the strips from the papyrus stalk.